The Predictive Role of Parathyroid Hormone for Nonalcoholic Fatty Liver Disease following Bariatric Surgery - Tannaz Jamialahmadi; Mohsen Nematy; Mohammed Abdalla; Ali Jangjoo; Ladan Goshayeshi; Matthew Kroh; Seyed Adel Moallem; Mitra Abbasifard; Thozhukat Sathyapalan; Amirhossein Sahebkar (Journal of Nutrition and Metabolism)
Background. Morbid obesity is frequently complicated by chronic liver diseases, including nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), and fibrosis. Parathyroid hormone (PTH) is found to be elevated in morbid obesity due to the defective hepatic metabolism of vitamin D. Bariatric surgery is performed to help patients with BMI>40 kg/m2 to effectively lose weight, particularly in patients with obesity who are afflicted with complications such as NAFLD/NASH. Objective. This study aimed to evaluate the PTH level as a predictor of hepatic function in individuals with morbid obesity who have undergone bariatric surgery. Methods. Ninety subjects with morbid obesity referred for Roux en-Y gastric bypass surgery were recruited. After IRB approval, demographic profiles, anthropometric factors, liver biopsy, and laboratory tests were obtained. The two-dimensional shear wave elastography (2D-SWE) technique was applied to assess hepatic stiffness. Results. A significant reduction occurred six months after bariatric surgery in the anthropometric indices p<0.001, hepatic elasticity p=0.002, alanine aminotransferase p<0.001, serum alkaline phosphatase p<0.001, gamma-glutamyl transpeptidase (GGT) p<0.001, and nonalcoholic fatty liver disease fibrosis score (NFS) p<0.001. Serum PTH concentration was not predictive of postsurgical liver fibrosis and steatosis at six months but could predict weight loss success rate. No significant alteration in serum PTH levels was observed between presurgical vs. postsurgical time points. Conclusion. A significant reduction was observed in the anthropometric parameters, liver enzymes, and hepatic elasticity after bariatric surgery. No significant effect was found on PTH levels.